Terrorism in Egypt: Analysis of the Narrative of Post-Arab Spring Terrorism - Ahmed Abdul (GoAcademica Research & Publishing, 2021)
Since the start of Arab Spring, the Middle East has witnessed the escalation of terrorism acts. Egypt even entered the emergency zone of terrorism after the fall of Muhammad Mursi from the presidency. Various groups of terror emerged in Egypt, among them is Anshar Bayt Al Maqdis who later joined ISIS and renamed Wilayat Sinai. This paper aims to analyze the transformation of terrorist groups by using instrumental and organizational theory. The findings of this research are that the ABM group is a transformation of pre-existing terror groups. It develop the organisation through delivering benefits, affiliations, competition, recruitment of members who use religious doctrine and take advantage of the economic and political conditions in the Sinai region.